PENERAPAN MODEL PROBLEM BASED LEARNING DAN PROJECT BASED LEARNING BERBANTUAN MEDIA INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Jihan Pratiwi; Nurlela; Devia Yola Triani; Putri Berliana Nauli; Indah Annisa Adha; Masitho Fitriyanti; Solbiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of student engagement and learning outcomes caused by teacher-centered conventional approaches has become a persistent challenge in Indonesian elementary education. This classroom action research (CAR) aimed to analyze the implementation of Problem Based Learning (PBL) and Project Based Learning (PJBL) models assisted by interactive media to improve student activity, creativity, and learning outcomes at SD Negeri 127 Palembang. A mixed-methods design was employed across two cycles involving 175 students from four classes (grades 1, 2, 4, and 5) selected purposively. Data were collected through structured observation, pre-tests and post-tests, student perception questionnaires, and documentation. In cycle one, PBL was applied using animated videos and digital quizzes as interactive media; in cycle two, PJBL led students to produce authentic projects supported by creative digital tools. Results showed that the average student learning score increased from 62.4 in the baseline to 72.8 at the end of cycle one and to 81.7 at the end of cycle two, with a completion rate of 84.2% surpassing the 75% target. Student activity rose from 34.2% to 78.9%. A paired t-test yielded t = 8.74 (p < 0.001) with Cohen's d = 0.87, indicating a large effect size. Integration of interactive media significantly strengthened student motivation and conceptual understanding. These findings confirm that PBL and PJBL, supported by interactive media, effectively develop 21st-century competencies critical thinking, creativity, collaboration, and communication in elementary school settings